Abundância de Panstrongylus geniculatus (Latreille, 1811) (Hemiptera: Reduviidae: Triatominae) e prevalência de infecção com tripanossomatídeos na Vila de Novo Remanso, Itacoatiara, Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
Chagas disease has as etiologic agent the flagellate parasite Trypanosoma cruzi, which 37 can be found parasiting several mammals species, including man. Transmission of T. cruzi 38 occurs naturally by individuals belonging to Triatominae subfamily (Hemiptera: Reduviidae). 39 At least 60 species of triatomines occur in Brazil, among them, Panstrongylus geniculatus 40 had the larger distribution, occurring in all regions of Brazil and other countries. Here we 41 estimated abundance of P. geniculatus related to micro-habitat characteristics and vegetation 42 descriptors, in the region of the village of Novo Remanso. The prevalence of infection in P. 43 geniculatus was inferred from parasitological examination of the intestinal contents and 44 molecular biology assay based on PCRc. Our results show that P. geniculatus is more 45 associated with the diameter of the trunk where it nests, than with the number of trunks or 46 distance to the edge of the forest or distance to nearest residence, and the prevalence of 47 infection by T. cruzi for the region is 72.4%.
Keywords: Doença de Chagas; Vila Novo Remanso; Panstrongylus geniculatus; CIÊNCIAS BIOLÓGICAS: ZOOLOGIA